2015
DOI: 10.1074/jbc.m115.692434
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use of Antibody Variable Region (Fv) Charge as a Risk Assessment Tool for Predicting Typical Cynomolgus Monkey Pharmacokinetics

Abstract: The pharmacokinetic (PK) behavior of monoclonal antibodies in cynomolgus monkeys (cynos) is generally translatable to that in humans. Unfortunately, about 39% of the antibodies evaluated for PKs in cynos have fast nonspecific (or non-targetmediated) clearance (in-house data). An empirical model relating variable region (Fv) charge and hydrophobicity to cyno nonspecific clearance was developed to gauge the risk an antibody would have for fast nonspecific clearance in the monkey. The purpose of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 43 publications
9
60
0
Order By: Relevance
“…Impressively, the optimized antibody displayed high specificity and excellent pharmacokinetic properties without reductions in affinity. These and related findings [4649] provide valuable insights for overcoming affinity/specificity trade-offs by engineering antibody CDRs and frameworks to achieve high specificity while maintaining high antibody affinity.…”
Section: Antibody Affinity/specificity Trade-offsmentioning
confidence: 95%
See 1 more Smart Citation
“…Impressively, the optimized antibody displayed high specificity and excellent pharmacokinetic properties without reductions in affinity. These and related findings [4649] provide valuable insights for overcoming affinity/specificity trade-offs by engineering antibody CDRs and frameworks to achieve high specificity while maintaining high antibody affinity.…”
Section: Antibody Affinity/specificity Trade-offsmentioning
confidence: 95%
“…The fact that measurements of antibody specificity (non-specific binding and self-association) are the best biophysical descriptors of the likelihood of antibody success in the clinic [67] highlights the importance of developing computational and bioinformatics methods for predicting antibody specificity. Some of the key factors that determine antibody specificity are becoming clearer, including the numbers of charged, hydrophobic and hydrophilic residues in CDRs [26, 27, 39, 41, 42, 44, 6870] as well as the net charge of the variable regions [46, 47, 49]. However, methods are needed to collectively describe these disparate findings and provide guidelines for identifying antibody variants with high specificity based only on their amino acid sequences or their combined sequences and structures.…”
Section: Future Directionsmentioning
confidence: 99%
“…This type of analysis can identify potential post‐translational modification hotspots (i.e., cysteines, asparagine/aspartate degradation, glycosylation sites, etc. ), assess charge and hydrophobicity, and model three‐dimensional structure. In vitro assays can be used to analyze mAb hydrophobicity using hydrophobic interaction chromatography, Fv‐FcRn interactions, and overall IgG integrity using FcRn affinity chromatography .…”
Section: Frequently Asked Questions On Pk Related Activities During Ementioning
confidence: 99%
“…1–4 Recent studies have also shown that changes in the charge distribution on the protein surface could alter mAb pharmacokinetics (PK) by affecting FcRn-IgG dissociation. 5,6 Thus, the potential risk of deamidation at each site needs to be evaluated to ensure product stability.…”
Section: Introductionmentioning
confidence: 99%